2012
DOI: 10.1038/eye.2011.364
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar hemodynamic parameters in open-angle and angle-closure glaucoma patients

Abstract: Purpose The purpose of this study is to compare the retrobulbar hemodynamic parameters in the ophthalmic artery (OA), central retinal artery (CRA), and posterior cilliary arteries (PCA), in open-angle glaucoma (OAG) and angle-closure glaucoma (ACG) patients. Patients and methods A total of 52 eyes from 52 patients with OAG and 25 eyes from 25 ACG patients who met the inclusion/exclusion criteria were included in this cross-sectional study. Peak-systolic velocity, end-diastolic velocity, and Pourcelot resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Chronic impairment of ocular blood flow with subsequent ischemia-reperfusion damage has been advocated as a major pathogenic factor. 23 Several instruments have been applied to inquire into ocular blood flow in glaucoma, including fluorescein and indocyanine green angiography, 24 laser speckle flowgraphy, 25 color Doppler imaging, 26 Doppler OCT, 27 confocal scanning laser Doppler flowmetry, 28 and retinal functional imager. 29 Although welcomed with great enthusiasm, none of these eventually broke Data are reported for controls (C), glaucoma suspects (GS), and glaucoma (G).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic impairment of ocular blood flow with subsequent ischemia-reperfusion damage has been advocated as a major pathogenic factor. 23 Several instruments have been applied to inquire into ocular blood flow in glaucoma, including fluorescein and indocyanine green angiography, 24 laser speckle flowgraphy, 25 color Doppler imaging, 26 Doppler OCT, 27 confocal scanning laser Doppler flowmetry, 28 and retinal functional imager. 29 Although welcomed with great enthusiasm, none of these eventually broke Data are reported for controls (C), glaucoma suspects (GS), and glaucoma (G).…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by the different pathogenic mechanisms of these two conditions. 13,23 PACG is characterized by uncontrolled IOP due to the mechanical obstruction of aqueous outflow, caused by the contact of the peripheral iris and the trabecular meshwork. On the other hand, although IOP is considered to be among the main risk factors for POAG, other factors may contribute to glaucomatous damage in POAG, especially in Asian populations where normal-tension glaucoma predominates.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, PACG is a disease entity that differs from POAG in terms of the clinical course and pathogenic mechanisms. 13 Higher IOP elevation is observed in PACG, and causes ischemic injury to various intraocular structures, for instance, the lens, corneal endothelium, and iris. Likewise, ocular perfusion can also be altered during the process of IOP elevation, which may directly cause deterioration in the peripapillary and macular microvascular perfusion.…”
mentioning
confidence: 99%
“…It was stated that RI provides important information regarding the status of blood circulation [26]. Besides, it has been shown that decreased blood flow velocities accompany the increased RI [13].…”
Section: Discussionmentioning
confidence: 99%